Design and activity of a cyclic mini-β-defensin analog: a novel antimicrobial tool - Scudiero O (Dove Medical Press, 2015)
Olga Scudiero,1,2 Ersilia Nigro,1 Marco Cantisani,3 Irene Colavita,1 Marilisa Leone,4 Flavia Anna Mercurio,4 Massimiliano Galdiero,5 Antonello Pessi,1 Aurora Daniele,1,6 Francesco Salvatore,1,2,7 Stefania Galdiero3,4 1CEINGE-Biotecnologie Avanzate Scarl, Naples, Italy; 2Dipartimento di Medicina Molecolare e Biotecnologie Mediche, 3Dipartimento di Farmacia, Università di Napoli Federico II, Naples, Italy; 4Istituto di Biostrutture e Bioimmagini, CNR, Naples, Italy; 5Dipartimento di Medicina Sperimentale, Seconda Università di Napoli, Naples, Italy; 6Dipartimento di Scienze e Tecnologie Ambientali Biologiche Farmaceutiche, Seconda Università di Napoli, Caserta, Italy; 7IRCCS Fondazione SDN, Naples, Italy Abstract: We have designed a cyclic 17-amino acid β-defensin analog featuring a single disulfide bond. This analog, designated “AMC” (ie, antimicrobial cyclic peptide), combines the internal hydrophobic domain of hBD1 and the C-terminal charged region of hBD3. The novel peptide was synthesized and characterized by nuclear magnetic resonance spectroscopy. The antimicrobial activities against gram-positive and gram-negative bacteria as well as against herpes simplex virus type 1 were analyzed. The cytotoxicity and serum stability were assessed. Nuclear magnetic resonance of AMC in aqueous solution suggests that the structure of the hBD1 region, although not identical, is preserved. Like the parent defensins, AMC is not cytotoxic for CaCo-2 cells. Interestingly, AMC retains the antibacterial activity of the parent hBD1 and hBD3 against Pseudomonas aeruginosa, Enterococcus faecalis, and Escherichia coli, and exerts dose-dependent activity against herpes simplex virus type 1. Moreover, while the antibacterial and antiviral activities of the oxidized and reduced forms of the parent defensins are similar, those of AMC are significantly different, and oxidized AMC is also considerably more stable in human serum. Taken together, our data also suggest that this novel peptide may be added to the arsenal of tools available to combat antibiotic-resistant infectious diseases, particularly because of its potential for encapsulation in a nanomedicine vector. Keywords: antimicrobial activity, cyclic mini-peptide, human beta-defensin